Cytotoxicity of the Aqueous Extract and Organic Fractions from Origanum majorana on Human Breast Cell Line MDA-MB-231 and Human Colon Cell Line HT-29 - Hanane Makrane; Mouhcine El Messaoudi; Ahmed Melhaoui; Mohammed El Mzibri; Laila Benbacer; Mohammed Aziz (Hindawi Limited, 2018)
The toxicity of the aqueous extract of Origanum majorana was tested (5 and 10 g/kg) in albino mice. No symptoms of toxicity or mortality were observed. The mice survived being active and healthy during all 14 days of observation. In addition, the weight measurement of the left and right kidneys, heart, and liver shows no significant difference between the control, 5 g/kg, and 10 g/kg. All extracts (aqueous, petroleum ether, dichloromethane, ethyl acetate, methanolic, and depleted aqueous extracts) of Origanum majorana tested against both types of cancer cells showed a more pronounced cytotoxic effect against breast cell line MDA-MB-231 than colon cells line HT-29 cells. The most marked effect is that of the ethyl acetate extract with IC50 30.90 ± 1.39 and 50.11 ± 1.44 (µg/ml), respectively. HPLC analysis of extracts from Origanum majorana showed that this plant contained polyphenols and flavonoids, which may be responsible for the biological activities found.